Daratumumab or active monitoring for high-risk smoldering multiple myeloma - Dimopoulos, Meletios A.; Voorhees, Peter M.; Schjesvold, Fredrik; Cohen, Yael C.; Hungria, Vania; Sandhu, Irwindeep; Lindsay, Jindriska; Baker, Ross I.; Suzuki, Kenshi; Kosugi, Hiroshi; Levin, Mark-David; Beksac, Meral; et al. (The New England journal of medicine, 2025)
Among patients with smoldering multiple myeloma at high risk for progression, progression-free survival at 5 years was 63.1% with daratumumab monotherapy, as compared with 40.8% with active monitoring.